Investigating age differences in e-mail pragmatic performance. (November 2018) - Barón, Júlia; Ortega, Mireia
Abstract: The present study analyzes openings and closings, requests and apologies in e-mail writing by EFL learners and English native speakers. It first aims to explore possible differences in pragmatic performance between EFL learners and English native speakers in order to identify the aspects that may lead to pragmatic inappropriateness when performing in the L2. Secondly, this study seeks to explore age effects on pragmatic competence. The participants were 40 Catalan/Spanish EFL learners and 40 English native speakers divided into two age groups (younger vs. older speakers). The participants had to write an e-mail to a teacher asking for the possibility of re-sitting an exam that they had missed. The results showed differences between younger EFL learners and younger English native speakers in all the pragmatic moves analyzed. No differences, however, were found when comparing the older groups. Further differences were identified when comparing younger and older EFL learners in their e-mail openings and their use of apologies. However, no differences could be found in the English native speaker groups. Some pedagogical implications are also suggested.